Cycled high hydrostatic pressure processing of whole and skimmed milk: Effects on physicochemical properties. (July 2020) - Yang, Shuailing; Liu, Guanchen; Munk, Daniel M.E.; Qin, Zihan; Petersen, Mikael A.; Cardoso, Daniel R.; Otte, Jeanette; Ahrné, Lilia
Abstract: In this study, we compare the effects of single- and double-cycle HP treatments at 600 MPa on inactivation of the natural microflora and physicochemical properties of whole and skimmed milk of high bacterial load. The results show that two-cycled HP (2 × 2.5 min) was more effective ( P   <   0.05 ) on microbial inactivation, and caused similar or slightly less changes ( P   >   0.05 ) in physicochemical properties of milk in comparison to single cycled HP (1 × 5 min). In addition to the expected milk protein structure changes, HP at 600 MPa caused only slight effects on milk fat and lactose. Minor decreases in levels of short chain fatty acids were observed with the cycled treatments, and the volatiles in general decreased after HP treatment, depending mostly on the pressure time but also on cycling in skimmed milk. The study confirmed the superior effect of two-cycle HP on microbial inactivation, and shows a slightly better preservation of the physical-chemical milk quality. Industrial relevance: Multi-cycling HP has been shown to be advantageous for microbial inactivation, but limited information is available regarding the effect on milk components in whole milk or skimmed milk. The present study compares the psychochemical properties of whole and skimmed milk processed by multi-cycling in comparison to single cycle HP treatment. Double cycled HP presented a superior effect on microbial inactivation and slightly better preservation of milk quality than one continuous HP. Highlights: Double HP cycling was more effective than single regarding microbial inhibition. Proteins were changed also by double HP treatment, but to a lesser extent. Aggregation of β-Lg increased with treatment time but independent of cycling. Casein micelle size decreased with treatment time but slightly less with cycling. No strong flavours formed but volatiles level depends on milk type and HP treatment.